Effects of life-work balance on health, according to gender, housing insecurity, and social class: an intersectional study - Constanza Vásquez-Vera; Ana Fernández; Carme Borrell (Springer, 2024)
Abstract The study aim was to analyse the differences in work-life balance between and within genders (1159 women, 1077 men, and 5 trans*), and their effects on health outcomes, according to housing insecurity, and social class. We measured five health outcomes: mental health, self-perceived health, sleep quality, chronic headaches, and chronic backpain. The explanatory variables were productive, reproductive workloads, and their interactions. Among women with housing insecurity, those with no productive workload and moderate reproductive workload had the poorest mental health, self-perceived health, and sleep quality. Among women without housing insecurity of non-manual social class, those with productive workload and high reproductive workload had the poorest mental health and sleep quality. Among men with housing insecurity, those with no productive workload and high reproductive workload had the poorest sleep quality and chronic backpain. The health effects of the work-life balance are not the same for all people and vary according to housing situation, social class, and gender.